Pengaruh Minat Belajar terhadap Kemampuan Membaca Bahasa Inggris Siswa - Ahyar, Miftahul Farid Mochamad; Hapsari, Fitri Senny; Isroyati, Isroyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the effect of interest in learning on the ability to read English Vocational High School students in Depok. The method used was a survey method with a total sample of 40 students taken by random sampling technique from three private vocational schools in Depok. Learning interest data collection uses a questionnaire in the form of a rating scale, while the ability to read English students is presented in the form of a written test with multiple choice questions. Both test instruments are first validated. Data analysis uses two-way analysis of variance (ANAVA) by first testing the normality and homogeneity tests. The results of the study there is a significant influence of interest in learning on the ability to read English students proven by the value of Ï value = 0.024 <0.05. In conclusion, student interest in learning has a significant effect on English reading ability. keywords; English, reading ability, interest in learning